Cost and morbidity analysis of chest port insertion in adults: Outpatient clinic versus operating room placement. (September 2017) - Feo, Claudio F.; Ginesu, Giorgio C.; Bellini, Alessandro; Cherchi, Giuseppe; Scanu, Antonio M.; Cossu, Maria Laura; Fancellu, Alessandro; Porcu, Alberto
Abstract: Background: Totally implantable venous access devices (TIVADs) represent a convenient way for the administration of medications or nutrients. Traditionally, chest ports have been positioned by surgeons in the operating room, however there has been a transition over the years to port insertion by interventional radiologists in the radiology suite. The optimal method for chest port placement is still under debate. Materials and methods: Data on all adult patients undergoing isolated chest port placement at our institution in a 12-year period were retrospectively reviewed. The aim of this cohort study was to compare cost and morbidity for chest port insertion in two different settings: outpatient clinic and operating room. Results: Between 2003 and 2015 a total of 527 chest ports were placed in adult patients. Of them, 262 procedures were performed in the operating room and 265 procedures were undertaken in the outpatient clinic. Patient characteristics were similar and there was no significant difference in early (<30 days, p = 0.54) and late complications (30–120 days, p = 0.53). The average charge for placement of a chest port was 1270 Euros in the operating room versus 620 Euros in the outpatient clinic. Conclusion: Our results suggest that chest ports can be safely placed in most patients under local anesthesia in the office setting without fluoroscopy or ultrasound guidance. Future randomized controlled studies may evaluate if surgeons or interventional radiologists should routinely perform these procedures in a dedicated office setting and reserve more sophisticated facilities only for patients at high risk of technical failure. Highlights: Chest ports can be safely placed under local anesthesia in the office setting. Fluoroscopy and ultrasound guidance are not necessary in the majority of cases. Port placement in the outpatient clinic is cost-effective.